PELAKSANAAN PERAN DALAM KELUARGA DI DESA SAWAH KECAMATAN KAMPAR UTARA (Studi Kasus Istri Sebagai Pencari Nafkah Utama Dalam Keluarga) - Roza Elva Nita; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Research on the implementation of the role of the family in the case study of wife as the main breadwinner in the family, in this study has the purpose to find out how the implementation role in the family as well as to know the role of retrieval decisions in the family. The location of this research lies in the Desa Sawah Kampar Utara Sub-district of Kampar Regency. This research used the qualitative method with descriptive analysis, namely data collection is obtained based on the data in field reality through observation, in-depth interviews and documentation. Informants of this research consists of four pairs of husband and wife, but the subject just in focus to his wife. The theory framework used in this research is the theory of family, role theory and decision making. The implementation of role in this research deals with the role of the public and domestic who are in families where the wife acts as the main breadwinner in the family. The role of the wife as the main breadwinner in the family make husbands more often were at home so that the occurrence of role Exchange between husband and wife. the wife has a more dominant contribution in meeting the needs of the economy of the family eventually affects decision-making in the family so the more dominating wife caused her role as breadwinner in family.Keywords: Public Role, The Role Of Domestic, Husband And WifeKata kunci: Peran Publik, Peran Domestik, Suami-Istri